Macrofauna Associated With a Rhodolith Bed at an Oceanic Island in the Eastern Tropical Pacific (Isla del Coco National Park, Costa Rica) - Solano-Barquero, Alberto; Sibaja-Cordero, Jeffrey A.; Cortés, Jorge (Frontiers in Marine Science, 2022)
Rhodoliths are round calcareous red algae that form extensive beds and associated with them are a diverse suite of species. Rhodolith beds are among the least known coastal-marine ecosystems, and even less is understood about their associated flora and fauna. Here we present an evaluation of the biodiversity larger than 500 microns associated with rhodoliths at Isla del Coco National Park, Costa Rica, an oceanic island in the Eastern Tropical Pacific, 500 km offshore of the mainland. This research determined the influence of rhodolith degree of aggregation (distance among individual rhodolith) as well as rhodolith complexity, volume, and mass in relation to the diversity, composition, and biomass of the associated fauna. A total of 145 taxa were collected in 60 rhodolith samples. Arthropods, polychaetes, and mollusks were the dominant taxa in terms of richness, crustaceans + acari represented >50 % of the total abundance. Five potentially new species were collected in this study. Collections identified 31 new records, with 20 of them, newly reported genera for Isla del Coco. Many of the organisms found were juveniles as well as adult stages bearing eggs, demonstrating the importance of this ecosystem. The faunal composition changed along the gradient of rhodolith aggregation. Moderately aggregated rhodoliths (separated by 5 to 10 cm) had the highest diversity, with the highest averages of taxon richness, total numerical abundance, and highest faunal biomass. There were more organisms in more complex rhodoliths; nevertheless, the complexity of the rhodolith did not affect the number of taxa or total organism biomass. Larger rhodoliths, in size and mass, favored higher amounts of taxa and organisms. The rhodoliths bed studied is an example of the intermediate disturbance hypothesis, because the highest value of biodiversity of invertebrates was at the moderate aggregation level of rhodoliths. In this density of rhodoliths, the fauna was less exposed to hard environmental conditions and prevented dominant species.